Marketing for academic libraries - Theodorou, Roxanna; Tsoubrakakou, Anastasia (Qualitative and Quantitative Methods in Libraries; Vol 5 No 1 (2016): March 2016 Issue, 2017)
Libraries all around the world are more and more adopting marketing techniques and concepts to better understand their users’ needs, to create meaningful services, to justify funding and expenses, to raise awareness, to communicate with external audiences, and generally become more visible and appreciated. The last few years, use of marketing has increased as budgets are shrinking and the needs of the users are becoming bigger and bigger. In Greece, though, although marketing is a very popular study field, it doesn't seem to find its place inside the Library community, as it’s often considered a far commercial concept for non-profit institutions. Additionally, academic libraries have an already established audience, which is going to seek their services, as they seem to have no other choice. But, as information production and dissemination methods change and evolve and more and more informational products make their appearance, Libraries have to study their users a lot more closely and possibly create new products, make them appealing and useful and offer them to the public. The aim of this paper is to identify marketing techniques that have already been used internationally focusing on the same target groups as Academic Libraries and that have helped to either design products and services that appeal to them as consumers or that have successfully promoted the message of the product and/or the brand to said community. It is widely accepted that a satisfied user is the best marketing tool for promoting library products and services. The question is if academic libraries need or use marketing techniques to improve their functionality creating innovative services. Marketing projects and promotional materials aren't just about convincing users to use a certain service. They also serve to change attitudes and preconceptions. Academic libraries, although they have a clearly defined audience, have a lot to gain by being more open and extrovert. More often than not, academic libraries seem to rely heavily on the fact that their users have limited choices when it comes to their information resources. Of course, this is not as much true as it was a little more than a decade ago. But still, a student or a researcher rely very much on the library services. The goal, however, for academic libraries would be to convince their users that their existence and services are not a “necessary evil” rather than a privilege and an opportunity. In order to gain that, thought, libraries should focus more on message design and branding, public relations, publicity and advertising. What this paper will try to do is identify some of the more successful (or notoriously unsuccessful) marketing campaigns that focus on the same target audiences as academic libraries. Next we will try to pinpoint and analyze the specific characteristics of these products and campaigns, which made them successful and communicated the message across by convincing and engaging the consumers. Finally, we will try to evaluate and determine which of those methods and characteristics can be adopted in the nonprofit environment of the academic libraries, and more specifically, by Greek academic libraries.